208 On-line assessment of environmental characteristics of paediatric bicycling injuries Alberta, Canada. (1st September 2016) - Farias, Mateus; Couperthwaite, Amy; Blanchard, Ian; Patel, Alka; Nettel-Aguirre, Alberto; Hagel, Brent
Abstract : Background: There are few studies on the relationship between the severity of bicycle-related injury in children and characteristics of the built environment. Methods: Emergency Medical Services (EMS) 9–1–1 calls completed between 2010–2013 in Calgary and Edmonton, Alberta, Canada for bicycle injury events in children <18 years old were identified. These data containclinical pre-hospital variables and were linked to administrative health outcome data using a deterministic linkage strategy. Events that required hospital admission were considered severe injuries. ArcGIS software was used to identify the EMS injury locations. Virtual environmental audits were done using the Pedestrian Environmental Data Scan (PEDS) with Google Maps. The personal characteristics of the injured bicyclists and the environmental characteristics of the injury locations were examined. Results: Among all paediatric EMS calls that were linked to a health care database, 575 involved bicycle injuries. To date, we have completed 157 location audits using the PEDS instrument with Google Maps. Analysis of audits completed to date indicates 83% of the subjects were male. Almost half (45%) of all injuries occurred on road segments with intersections. Two-thirds of injuries occurred at locations with a lack of street crossing aids. Conclusions: We have made progress toward profiling the individual and environmental characteristics of bicycle injuries. Next steps involve completing this process for the remaining injury locations. Injuries requiring hospital admission (i.e., severe injuries) will be compared with the ones that did not (i.e., non-severe injuries) for personal (e.g., age, sex) and location (e.g., presence of intersection) variables.